Comparison between incremental shuttle run test and Harvard’s step test on peak exercise performance in healthy males: a cross-sectional study - Gondane, Supriya; Retharekar, Seemi A.; Kudalkar, Swaroop V. (International Journal of Research in Medical Sciences, 2019)
Background: Cardiovascular fitness is directly related to the physical health of the person. Aerobic capacity (VO2max) is one of the major criteria to decide the cardiovascular fitness of an individual. To help quantify the fitness level by calculating their VO2max, there are various indirect maximal tests available but out of these, which one would predict VO2max better, is a major concern. Hence the purpose of this study was to compare the effects of two indirect maximal tests i.e. Incremental Shuttle Run Test (ISRT) and Harvard’s Step Test (HST) on peak exercise performance in young healthy males. Methods: A cross-sectional study with purposive sampling was performed on healthy untrained 100 males of age group 18-25 years. Day 1 subjects performed ISRT on 20 m track and after a 48 hours rest period, on day 3 same subject performed Harvard’s step test. Pre and post-test parameters (Pulse rate, respiratory rate, systolic and diastolic blood pressure and RPE) were measured and predicted VO2max was calculated. Results: Post-test parameters i.e. PR, RR, SBP significantly increased (p=0.00*) by Harvard’s step test. The diastolic blood pressure did not change significantly (p=0.3) for both the tests. Rating of perceived exertion by both the test was of the range 17-19 (very hard to maximal). Calculated predicted VO2max was significantly more by ISRT than HST in males (p=0.00*). Conclusions: Incremental shuttle run test is more efficient in predicting VO2max than Harvard’s step test in healthy adult’s males.